Population Genetic Analysis of Phytophthora colocasiae from Taro in Japan Using SSR Markers - Jing Zhang; Ayaka Hieno; Kayoko Otsubo; Wenzhuo Feng; Koji Kageyama (Journal of Fungi, 2023)
Phytophthora colocasiae is an important pathogen that causes great economic losses in taro production in tropical and subtropical regions, especially in Japan. Understanding the genetic variations in P. colocasiae populations and their transmission patterns in Japan is essential for effective disease control. Here, the genetic diversity of 358 P. colocasiae isolates, including 348 from Japan, 7 from China, and 3 from Indonesia, was assessed using 11 simple sequence repeat (SSR) primer pairs with high polymorphism. The phylogenetic tree of the SSR locus showed that the isolates from Japan could be divided into 14 groups, with group A being the dominant group. Among foreign isolates, only six from mainland China were similar to those from Japan and clustered in groups B and E. Analysis of molecular variance (AMOVA), principal components analysis (PCA), and cluster analysis (K = 3) results revealed a moderate level of genetic diversity, mainly within individuals. Populations showed high heterozygosity, a lack of regional differentiation, and frequent gene flow. Analysis of mating types and ploidy levels revealed that A2 and self-fertile (SF) A2 types and tetraploids were dominant across populations. Explanations and hypotheses for the results can provide more effective strategies for disease management of taro leaf blight.